IMPROVING THE EFFICIENCY OF RESOURCE MANAGEMENT OF PRODUCTION IN MODERN CLUSTERS - Khayitova Iroda Naimovna; Aslanov Abdullo Khojimurodovich (Galaxy International Interdisciplinary Research Journal, 2023)
The resource management of production in modern clusters plays a crucial role in ensuring business efficiency and success. Effective resource management ensures that the right resources are allocated to the right tasks at the right time. This article explores various strategies and approaches to enhance the efficiency of resource management in modern clusters.